A giant bezoar in a child with cerebral palsy – could we prevent the disease? - Łuczak, Justyna; Bagłaj, Maciej; Polok, Marcin (Pediatria Polska - Polish Journal of Paediatrics, 2019)
We present a case of giant bezoar in a 16-year-old boy with cerebral palsy. Endoscopy failed to remove the mass. Laparotomy revealed that the stomach, small intestine, and colon were full of cloth material. It was extracted by multiple enterotomies. A fifty-centimetre section of the small intestine was resected due to pressure necrosis. The bezoar mass in the stomach did not tightly fill its space. It was extracted by gastrotomy. Rising awareness among parents and healthcare professionals about the possible treatment of compulsive behaviours might prevent serious complications. We opt for laparotomy if oesophagoduodenoscopy fails to remove the bezoar entirely or in case of an unremarkable bezoar mass in the stomach associated with evident preoperative intestinal obstruction symptoms.